Variable retention management influences biomass of Misodendrum and Usnea in Nothofagus pumilio southern Patagonian forests - Soler Esteban, Rosina Matilde (2014)
Variable retention system (retention of some existing trees in different densities and significant elements of the original forest after logging) aims to mitigate the impact of harvesting in temperate native forests, improving the biodiversity conservation in managed stands. This work evaluates the effect of variable retention harvesting on epiphytic lichen (Usnea barbata) and mistletoe (Misodendrum punctulatum) in Nothofagus pumilio forests. We quantified the litter fall of lichen, mistletoe and trees monthly for three years. Tree and lichen biomass were influenced by canopy cover, being higher in primary forests than in harvested stands. But aggregated retention showed highest mistletoe biomass production. Furthermore, mistletoe biomass increased while lichen biomass decreased over the years after harvesting. Variable retention was useful to maintain both lichen and mistletoe after harvest, but aggregated was not enough to maintain the original level of lichen populations. It is necessary to evaluate positive (litter input) and negative effects (decline host growth) of mistletoes and epiphytic lichens at community level for management decisions. Forest harvesting with variable retention generate positive (litter input) and negative effects (decline host growth) of mistletoes and epiphytic lichens at community level, which can be evaluated during conservation and management planning.